2016
DOI: 10.1155/2016/4286576
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Parasite Burden in Children with Falciparum Malaria and Bacteremia Coinfections: Role of Mediators of Inflammation

Abstract: Bacteremia and malaria coinfection is a common and life-threatening condition in children residing in sub-Saharan Africa. We previously showed that coinfection with Gram negative (G[−]) enteric Bacilli and Plasmodium falciparum (Pf[+]) was associated with reduced high-density parasitemia (HDP, >10,000 parasites/μL), enhanced respiratory distress, and severe anemia. Since inflammatory mediators are largely unexplored in such coinfections, circulating cytokines were determined in four groups of children (n = 206… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 63 publications
5
30
1
Order By: Relevance
“…This is consistent with studies that reported low production of IFN-γ, low response of T cells to some mitogens and increased T reg cells in cord blood of neonates born to women with placental malaria [43][44][45][46][47]. These alterations in the host immune response, associated with microscopic P. falciparum malaria, result in increased susceptibility to bacteraemia in children [48,49] and alteration of the vaccine response [7,9,50]. Therefore, it is essential in future to evaluate the effect of submicroscopic maternal infections in our setting on the immunity of neonates and children post-vaccination.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with studies that reported low production of IFN-γ, low response of T cells to some mitogens and increased T reg cells in cord blood of neonates born to women with placental malaria [43][44][45][46][47]. These alterations in the host immune response, associated with microscopic P. falciparum malaria, result in increased susceptibility to bacteraemia in children [48,49] and alteration of the vaccine response [7,9,50]. Therefore, it is essential in future to evaluate the effect of submicroscopic maternal infections in our setting on the immunity of neonates and children post-vaccination.…”
Section: Discussionsupporting
confidence: 90%
“…As expected in this young cohort, the frequency of comorbid conditions was low across the GNI categories except for anemia, which was present in 24% of the patients in LLMIC. The anemia seen in LLMIC patients may be a marker for prevalent malnutrition, chronic infection and/or endemic malarial and parasitic disease, which in turn might impact the incidence and outcome of AKI in this population [ 27 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Co-infections with bacteria and malaria parasites are common life-threatening conditions in children residing in sub-Saharan Africa (36). It has been reported that the most frequently isolated G + and Gram-negative (G − ) bacteria found from 206 children aged 3-36 months in Kenya are Staphylococcus aureus (G + bacteria) and non-Typhi Salmonella (G − bacteria), respectively (36).…”
Section: The Roles Of Ifn-i In Co-infection With P Falciparum and Bamentioning
confidence: 99%
“…Co-infections with bacteria and malaria parasites are common life-threatening conditions in children residing in sub-Saharan Africa (36). It has been reported that the most frequently isolated G + and Gram-negative (G − ) bacteria found from 206 children aged 3-36 months in Kenya are Staphylococcus aureus (G + bacteria) and non-Typhi Salmonella (G − bacteria), respectively (36). Kenyan children co-infected with G − bacteria and P. falciparum can increase clinical outcomes such as malnutrition, respiratory distress, anemia, and mortality, although bacteremia is associated with reducing incidences of high-density parasitemia (37).…”
Section: The Roles Of Ifn-i In Co-infection With P Falciparum and Bamentioning
confidence: 99%
See 1 more Smart Citation